تعليم اللغة العربية في المعهد السلفي و المعهد الحديث نماذجا - Hasyim Asy’ari; Ammar Zainuddin (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2018)
Islamic boarding schools are Islamic educational institutions that focus on moral education. Islamic boarding schools at this time were divided into ancestor and modern boarding schools. There are differences in the curriculum and learning models of Arabic in the two pesantren. Salaf Islamic boarding schools have a special curriculum in understanding the understanding of Islam. Learning Arabic in the Salaf Islamic boarding school is oriented towards grammatical learning by memorizing the terms nahwu and shorof and memorizing nadhom. While the Arabic language learning curriculum in modern pesantren aims not only for religious scholarship, but aims to use all language skills in communication. This Islamic boarding schools believes that language learning activities must provide students the ability to communicate correctly, both in oral and written form.